The Role of Technology as Material Innovation in Interior Design Industry - Adisti Ananda Yusuff; Indra Gunara Rochyat (Gestalt : Jurnal Desain Komunikasi Visual, 2022)
The development of knowledge, generally still works with the development of technology in the modern age of technology all the nice aspects in our life. Almost all of science a thriving now by various technologies to improve and develop the existing. In the interior design, the role of material is important to provide for changes in work done. Now material development in industry interior design developed rapidly. Many materials that bring freshness to the industry. The use of material waste into one of the trends is being widely interested in the community this the modern era, with lifestyles called the green lifestyle made material with recycling system into one way for. In industry, a recycled material made bio-composite board is one of the ways. In order to increase the sale price of waste in, higher than ever. Manufacturing a bio-composite are running in parallel with the use of technology is, the use cold to be alternating press technique in the manufacturing process. This technology also makes the result of waste processing as the planks of bio-composites according to the standard of the quality of already existing at the present time. experimental method is used to study the bio composite waste product. The discussion of the role of technology in the innovation material in the interior design especially in its suspected uranium-based bio-composite material board waste will be discussed at great length.